(untitled) (Research, Society and Development, 2020)
The limitations and difficulties inherent to the socioeconomic context in Brazil, and the constant changes in labor relations incite changes in the work-professional interests of nursing. Thus, new perspectives and opportunities influence the labor market of this professional body from the development of their own businesses. The objective was to identify in the scientific literature the challenges, potentialities and perspectives of entrepreneurial entrepreneurship for nursing. This is an integrative review carried out between the months of October 2018 and May 2020, by the controlled search paired with data from the Virtual Health Library. The descriptors in health sciences used were "nursing" and "entrepreneurship" with the addition of the Boolean operator “and”; associated with the use of filters: full text available; type of document scientific articles; without time frame of publication. The study population makes up 29 documents, 12 of which are used as a sample. The integrative review protocol was previously prepared using an instrument validated by Ursi (2005). Secondary data were organized into categories and analyzed with descriptive support from the scientific literature. Entrepreneurship in nursing is in full growth, and is home to multidisciplinary knowledge, it is an emerging research field that demands scientific theories aimed at nursing practices. The bureaucratic issue was highlighted as a hindering factor for the professional class enterprise. Thus, it is essential to awaken the entrepreneur’s interest in nurses since graduation; so that academics can see in an expanded way the potential of the job market possible to the profession.